Infección del tracto urinario y preeclampsia en gestantes atendidas en el Hospital Regional de Loreto entre enero 2019 - diciembre 2020 - Huansi Panduro, Luz Amalia (2022)
INTRODUCTION. (UTI) Urinary tract infection; is the existence of germs capable of producing functional and morphological alterations in the bladder, collecting systems or kidneys. Most cases with UTI depend on the many maternal and epidemiological factors that will be evaluated, as well as associated with Preeclampsia Disease (PD). It has been defined as the presence of proteinuria> 300 mg, plus arterial hypertension ? 140/90 after the 20th week of gestation as minimum criteria. Its causes are various maternal alterations, to this are added the absence of prenatal controls, for the main reason that brought the COVID 19 pandemic and the increase in the health crisis in addition to the limited access to health services. Some world reports evidenced 19 cases of UTI during pregnancy with a high risk factor for the development of PD. Therefore, this study aims to strengthen the knowledge of the direct and indirect impact of UTI in patients with Preeclampsia, in order to reduce maternal-fetal complications and risks. OBJECTIVE. To determine the association between urinary tract infection and preeclampsia in pregnant women treated in the obstetrics and gynecological service of the Hospital Regional De Loreto "Felipe Santiago Arriola Iglesias" in the period January 2019 to December 2020. METHODOLOGY. Retrospective, cross-sectional, descriptive and quantitative study; The sample consisted of 85 pregnant women treated at the “Felipe Santiago Arriola Iglesias” Regional Hospital of Loreto, treated with the inclusion criteria. Only those with incomplete medical records were excluded. The type of sampling was non-probabilistic and the census technique because the entire population was considered. RESULTS: Once the approval of the investigation project has been obtained, the evaluation and permission will be requested from the research committee and committee of the Regional Hospital of Loreto. For data collection, the medical records were analyzed using the data collection form with the SPSS 25 software, where descriptive statistics will be applied, presenting the results in absolute and relative frequency tables with graphs in Excel 2013. CONCLUSION: They will be obtained according to the results.